ChemInform Abstract: One‐Pot Synthesis of Amides from Aldehydes and Amines via C—H Bond Activation. Issue 8 (1st March 2013) - Cadoni, Roberta; Porcheddu, Andrea; Giacomelli, Giampaolo; De Luca, Lidia
Abstract Aliphatic and aromatic aldehydes and a series of mono‐or disubstituted amines can be used for the process.